PENGEMBANGAN KOMIK DIGITAL MATERI SISTEM EKSKRESI PADA MANUSIA BAGI PESERTA DIDIK KELAS XI DI SMA NEGERI 1 SUWAWA - Lamondo, Djuna; Hulukati, Fauzia; Nur Akbar, Muh.; M. Hasan, Ani; Dama, Lilan; Solang, Margaretha (Jurnal Biogenerasi, 2024)
This research aims to determine the validity and practicality of developing digital comics regarding human excretory systems for class XI students at SMA Negeri 1 Suwawa. This research is classified as development research using the 4D model, with trials on 20 students in class XI – A SMA Negeri 1 Suwawa. The results of the research show that: (1) The validity test of digital comic media based on percentages obtained a score of 96.35% (Very valid), and the material validity test based on percentages obtained a score of 97.91% (Very valid), (2) The practicality test consisted of from the implementation of learning, student responses and teacher responses. The learning implementation test at the first meeting to the second meeting based on percentage obtained a score of 87.5 (Very good), the student response test based on percentage obtained a score of 86.50 (Very good), and the teacher response test based on percentage obtained a score of 96.87% ( Practical).